Riders - Rossi, Veronica (Tom Doherty Associates, 2016)
After regaining consciousness from a seemingly fatal accident, eighteen-year-old U.S. Army Ranger Gideon Blake discovers that he is War, one the legendary Four Horsemen of the Apocalypse, and together with Conquest, Famine, and Death, must save humanity from an ancient evil.